The construction of Palestinian Muslim masculinities in two novels by Laila Halaby and Randa Jarrar. Issue 3 (3rd July 2019) - Maloul, Linda F.
ABSTRACT: Past, and more significantly, post 9/11 Anglo-American political and popular culture representations of Arab Muslim masculinities in general and Palestinian masculinities in particular as evil, violent and terrorizing produced the myth of the Arab Muslim masculine evil: an ahistorical image of Arab and Muslim men that reduces them to a few negative, sometimes contradictory, characteristics. An understanding of politics and cultural productions as inextricably linked can explain the reasons behind the strength and sustainability of these negative stereotypes. In addition, it explains why Arab American writers find fiction an appropriate medium to produce diverse images of Arabs, Muslims and Arab Americans. This article draws primarily on Daniel Monterescu's models of hegemonic Palestinian masculinities which follow Raewyn Connell's model of hierarchical masculinities to explore the ways by which Laila Halaby's West of the Jordan (2003) and Randa Jarrar's A Map of Home (2008) offer complex Palestinian Muslim masculinities, particularly in the domestic sphere. These masculinities are positioned within specific historical, socio-political and cultural realities, which are not solely governed by narrow definitions of Islam. Palestinian Muslim masculinities in both novels challenge monolithic and essentialist representations of Arab Muslim men in general and Palestinian men, particularly after the events of 9/11.